POLYGAMY IN THE INDONESIAN MARRIAGE LAW SYSTEM - Sri Rizki; Sufirman Rahman; Said Sampara (P3M Stia Al Gazali Barru and Meraja media, 2020)
Abstract [Full Paper] to pdf Copyright (c) 2020 Meraja journal